2017
DOI: 10.1155/2017/3189412
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Schemes by Variables Inspection for the First-Order Autoregressive Model between Linear Profiles

Abstract: We present four new sampling schemes by variables inspection to deal with the first-order autoregressive model between linear profiles. The first plan is based on exponentially weighted moving average (EWMA) and the rest of three plans are using the resubmitted sampling, repetitive group sampling (RGS), and multiple dependent state (MDS) sampling schemes. The nonlinear optimization problem is developed to find the number of profiles and the corresponding acceptance criteria, such that the producer's and consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This section looks at the circumstance where the supplier is permitted to ask for resampling when a lot is not accepted. For linear profiles [11] and auto-correlated linear profiles [15] proposed resubmitted sampling plans based on the yield index. Both authors found the resubmitted sampling plan has a better-operating characteristics curve (OC) compared to a single sampling plan.…”
Section: Proposed Sampling Plans a Resubmitted Sampling Planmentioning
confidence: 99%
See 3 more Smart Citations
“…This section looks at the circumstance where the supplier is permitted to ask for resampling when a lot is not accepted. For linear profiles [11] and auto-correlated linear profiles [15] proposed resubmitted sampling plans based on the yield index. Both authors found the resubmitted sampling plan has a better-operating characteristics curve (OC) compared to a single sampling plan.…”
Section: Proposed Sampling Plans a Resubmitted Sampling Planmentioning
confidence: 99%
“…If the test is costly and destructive the RGS plan takes a sequence of small samples from the lot and allows the number of repetitions (rp) to be determined entirely by the results of the sampling process. For the first-order autoregressive between linear profiles [15] proposed RGS plan. The RGS plan for AR(1) nonlinear profiles based on S pkA:P is given as follows:…”
Section: B Repetitive Group Sampling Planmentioning
confidence: 99%
See 2 more Smart Citations